2020
DOI: 10.7759/cureus.12126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Depression Among Acne Vulgaris Patients Treated With Isotretinoin

Abstract: Background Isotretinoin is the most effective treatment for moderate to severe acne. However, isotretinoin has many side effects related to its use. Since 1983, when Hetzen reported the first occurrence of new depressive symptoms in patients treated with isotretinoin, a lot of controversies emerged regarding the causal relationship between isotretinoin and depression. Objective To evaluate depression among acne patients treated with isotretinoin versus doxycycline at King Fahad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This evidence-based review demonstrated that treatment of acne patients with isotretinoin does not appear to be related to the development of depression, with a strength of recommendation of A 3,4,[6][7][8] . We further conclude that treatment of acne, regardless of chosen drug, seems to improve depressive symptoms 3,6,7 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…This evidence-based review demonstrated that treatment of acne patients with isotretinoin does not appear to be related to the development of depression, with a strength of recommendation of A 3,4,[6][7][8] . We further conclude that treatment of acne, regardless of chosen drug, seems to improve depressive symptoms 3,6,7 .…”
Section: Resultsmentioning
confidence: 90%
“…After a detailed analysis of the included studies, we found that there is no evidence that isotretinoin is associated with depression 3,4,[6][7][8] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study conducted in Venezuela by Suarez et al implies that Isotretinoin is safe to use with respect to psychological side effects [ 15 ]. The cohort and nested case-time-control study in France by Droitcourt et al and the cohort prospective, questionnaire-based study conducted in Saudi Arabia by Algamdi et al suggest that is no association between Isotretinoin and depression [ 18 , 19 ]. The systematic review and meta-analysis by Huang et al in Taiwan also suggest the same [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…A cohort prospective, questionnaire-based study was conducted in Saudi Arabia by Algamdi et al from November 2019 to March 2020 on 29 patients [ 19 ]. The subjects included in this study were moderate to severe acne patients aged 18-30 years.…”
Section: Reviewmentioning
confidence: 99%